PERANCANGAN APLIKASI INVENTORY BARANG BERBASIS WEBSITE SEBAGAI PENCATATAN BARANG PADA CV LANGGENG JAYA LESTARI: DESIGN OF A WEB-BASED INVENTORY APPLICATION FOR GOODS RECORDING AT CV LANGGENG JAYA LESTARI - Nurika Sefira Lestari; Imam Tahyudin; Dinar Mustofa (LPPM Universitas Abdurrab, 2026)
This study aims to design and develop a web-based inventory system for CV Langgeng Jaya Lestari using the Design Thinking method, which consists of empathize, define, ideate, prototype, and test stages. The system was developed to improve manual inventory management into a more computerized and efficient process. The main features include recording incoming goods, outgoing goods, stock monitoring, and integrated inventory data management through a single dashboard. Data collection was carried out through observation and interviews with the company to identify system requirements. The results show that the inventory website improves efficiency and accuracy in managing stock data. System testing was conducted using alpha testing based on expert judgment involving the company leader of CV Langgeng Jaya Lestari and a website expert. The evaluation resulted in an average score of 85.14 out of 100, categorized as very good. This indicates that the system meets user requirements and is feasible to use, although further improvements are still needed for future development and optimization..